Entrepreneurial leadership and workforce efficiency among micro-enterprises (MES) in Southwest, Nigeria - Ismaila, Yusuf; Rahman, Mustapha; Muritala, Opatola Abolade (Management and Entrepreneurship: Trends of Development, 2025)
In the manufacturing sector, entrepreneurial leadership particularly in micro-enterprises is believed to have a major impact on workers’ efficiency, boosting output and performance. However, the majority of Nigerian micro-businesses seem to have inefficient employees, which has an impact on the business’s overall success. Micro-businesses in southwest Nigeria need a way to boost employees’ productivity and boost overall performance, and this can be achieved through entrepreneurial leadership. This study’s primary goal is to investigate how workforce efficiency in micro-enterprises in Southwest Nigeria is affected by entrepreneurial leadership. The study employed a cross-sectional survey research approach. 398 respondents were chosen for the study using convenient and purposeful sampling approaches. A closed-ended questionnaire was used to collect the data, and PLS-SEM was used for analysis. A t-value of 7.40 and a p-value of 0.000 indicate that the results demonstrated that entrepreneurial leadership significantly affects the workforce efficiency among micro-enterprise owner-managers in Southwest Nigeria’s manufacturing sector. According to the study’s findings, micro-business owners and managers who value and embrace entrepreneurial leadership will be able to stay ahead of the curve in terms of consumer trends and shifts, carve out distinctive niches in crowded markets, and maintain workforce efficiency; all of which are critical components of a firm’s competitiveness. The study suggests that in order to face dynamic global business issues and maintain market competitiveness, companies should support entrepreneurial leadership as a contemporary and millennium idea that would enhance workers’ performance effectively and efficiently. JEL Classification: L26, J24, M12, O15